Impact of inferior vena cava obstruction during orthotopic liver transplantation without venovenous bypass grafting on early postoperative renal function (pilot analysis) - Ye. O. Santotsky; A. F. Minov; D. I. Yurlevich; L. V. Kirkovsky; S. V. Korotkov; D. P. Kharkov; L. S. Bolonkin; Yu. V. Slobodin; Ye. L. Avdei; A. M. Fedoruk; A. M. Dzyadzko; A. Ye. Shcherba; et al. (Трансплантология (Москва), 2018)
Ligation of the inferior vena cava (IVC) during classical orthotopic liver transplantation (OLT) may be followed by pronounced hemodynamic changes and may provoke renal dysfunction. The authors have examined the impact of IVC ligation during OLT without venovenous bypass grafting on early postoperative renal function in 6 patients. The Cockcroft-Gault formula was used to evaluate renal function from the creatinine clearance on postoperative days 1, 3, 7, and 10. The endogenous creatinine clearance was diminished within the first 24 hours after surgery; this was 68.2±18.1 (24.3—146) ml/min and significantly correlated with that before OLT, with the mean blood pressure (BPmean) in the icteric period, and with age. At the same time, icteric BPmean was in the normal range — 77.2±1.59 (71.6—81.6) mm Hg and clinical renal failure developed in a female patient with significant preoperative renal dysfunction. Thus, IVC ligation at OLT with IVC interposition in the study contributed to a lower endogenous creatinine clearance within the first 24 postoperative hours, but results in no clinical renal function aggravation.